Developing Kinemaster-based Podcast Media to Increase Student Motivation to Learn the History of Islamic Culture at Mts 1 Palu City - Muhayanah, Luluk; Maimun, Agus (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Creative use of media will increase the possibility for students to learn more, embed what they learn better, and improve performance in carrying out skills according to learning objectives. Podcast media has recently become the most popular media and is one of the choices of teachers in supporting teaching and learning activities. This study aims to increase student learning motivation through the use of the kinemaster application in making podcasts on SKI class VII MTS Negeri 1 Palu City. This development research method was carried out using the ADDIE Research and Development (R&D) concept. The results of the study show that the KineMaster application-based podcast learning media has proven to be successful because the developed media is able to present messages and stimulate learning. This is evidenced by the increase in student learning motivation which is classified as high. The conclusion from this study is that the kinemaster application-based podcast learning media is able to foster student learning motivation, it can be said that this learning media has succeeded in stimulating students to learn.